2009
DOI: 10.1007/bf03181939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rounded edged dimple arrays on the boundary layer development

Abstract: The effect of a turbulent boundary layer subjected to a series of rounded edged shallow dimple arrays with dimple depth ratios, d/D of 4%, 8% and 12% were experimentally studied. Measurements show the existence of a higher flow speed region at the center of each dimple. The spanwise distribution of the mean wall shear stress immediately downstream of the centers of the last row of dimples does not vary with dimple depth, and is about 45% over that without the dimple array. Turbulence measurements and surface f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…It has been shown that dimples are able to generate streamwise vortices which in turn introduce spanwise flow components near the wall. 24 We postulate that the streamwise vortices generated by passive dimples can achieve the same drag reduction effect as those generated by active oscillating wall or transverse jets. The objective of the present paper is to establish such drag reduction using streamwise pressure measurement and to investigate the possible role of these streamwise vortices on the effect of drag reduction using hot-wire measurement.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that dimples are able to generate streamwise vortices which in turn introduce spanwise flow components near the wall. 24 We postulate that the streamwise vortices generated by passive dimples can achieve the same drag reduction effect as those generated by active oscillating wall or transverse jets. The objective of the present paper is to establish such drag reduction using streamwise pressure measurement and to investigate the possible role of these streamwise vortices on the effect of drag reduction using hot-wire measurement.…”
Section: Introductionmentioning
confidence: 98%
“…As a result, hot gas-contacting turbine blades have to be cooled intensively by using various cooling techniques, such as internal convective cooling [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and film cooling [21][22][23][24] on the blade exterior, in order to ensure a good structural integrity of the turbine blades. Dimple arrays, which can be placed throughout the entire internal cooling passage of turbine blades incorporating with other augmentation methods (such as impingement holes, rib turbulator, and pin-fins), have become a magnet in forced convective heat transfer studies in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Due to its good heat transfer enhancement performance with comparatively smaller pressure loss penalties in comparison to other types of heat transfer augmentation devices such as pin-fins and rib tabulators, a dimpled surface (i.e., a flat surface with dimple arrays) provides a desirable alternative for the...…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental and numerical studies have been conducted in recent years to investigate heat transfer augmentation performance of dimpled surfaces [3][4][5][6][7][9][10][11][12][13][15][16][17][18][19]. It is found that the heat transfer performance of a dimpled surface is greatly affected by the configuration of the dimples, including dimple diameter, dimple depth ratio, distribution pattern, and shape of the dimples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations